2016
DOI: 10.11604/pamj.2016.23.261.8414
|View full text |Cite
|
Sign up to set email alerts
|

Value of training on motivation among health workers in Narok County, Kenya

Abstract: IntroductionTraining, as an additive human resources intervention is decisive to organizational performance. Employees require constant update of formal and informal knowledge alongside positive attitudes that have been defined as necessary in motivation leading to effectiveness in performance hence workplace training is tied to achieving organizational aims and objectives. The objective of this study was to determine the influence of training on motivation among health workers in Narok County, Kenya.MethodsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 17 publications
3
32
0
1
Order By: Relevance
“…9, No. 1; conscientiousness, timeliness, and attendance (Momanyi et al, 2016). Findings were similar to those made in District hospitals in Kenya where studies reported that the majority of respondents strongly agreed to being hard workers and disagreed that they were often absent from work, while many participants described themselves as demotivated (Mbindyo et al, 2009).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…9, No. 1; conscientiousness, timeliness, and attendance (Momanyi et al, 2016). Findings were similar to those made in District hospitals in Kenya where studies reported that the majority of respondents strongly agreed to being hard workers and disagreed that they were often absent from work, while many participants described themselves as demotivated (Mbindyo et al, 2009).…”
Section: Discussionsupporting
confidence: 70%
“…The motivation level of HWs in Narok County has been evaluated elsewhere and found out to be average (Momanyi et al, 2016), suggesting wide variation in the general motivation of the HWs across health systems settings. These variations may be explained by differences in levels of factors contributing to motivation, as well as differences in health care environments (Momanyi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the study survey, it was noted that there were many challenges facing health industry in Narok County [22][23][24]. Addressing these 21 challenges is not an easy task in any ways as outlined by [25,[22][23][24]. This is an indicator of how the nursing workforce is complex, in a state of confusion and compounded with a series of problems, which require a well thought out comprehensive system of analysis in order to help approximate to sustainable solutions.…”
Section: Challenges In Nursing Industry In Narok Countymentioning
confidence: 99%
“…Approaches to any one of the above challenges should be holistic in nature and therefore may require concerted efforts from all types of human resources in the society in order to rise to the challenges [26]. were not considered in the analysis due to the fact that they featured only once or twice in literature [22][23][24].…”
Section: Challenges In Nursing Industry In Narok Countymentioning
confidence: 99%